Top management turnover and firm default risk: Evidence from the Chinese securities market - Wei Ting (China Journal of Accounting Research, 2011)
China has moved rapidly from a socialist planned economy to a market economy. As a result, many enterprises in China are seeking talented top management to increase their performance and decrease their default risk. Studies abound regarding top management turnover and its relationship with firm performance, however, few studies have connected top management turnover with firm default risk. In China, a market with extensive financial fraud, firm default risk is an important factor and thus we explore this relationship in the Chinese securities market. Our results indicate that firms with higher default risk are more likely to change their top management in the next financial reporting period. In addition, following changes in top management, such firms default less than other companies.
Keywords: G32; G15; M41; K23; F51; 650; Top management turnover; Firm default risk; Chinese securities market